Childhood among Crocodiles: Using Playing and Drawing As Research Tools of A Human-Animal Relationship in Bazoule, Burkina Faso - Catu, Adrian (Journal of Community Positive Practices, 2022)
Stemming from a multi-species ethnographic research on the cohabitation between humans and crocodiles in village of Bazoulé, Burkina Faso, the article describes the use of play and drawing as research instruments for understanding how children see crocodiles, the precepts informally transmitted to them by adults about this animal and, ultimately, the unverbalized perception of this human community about crocodiles.